2020
DOI: 10.1164/rccm.202005-1706le
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Visitation Policies and Communication Practices in Michigan ICUs during the COVID-19 Pandemic

Abstract: Critically ill patients are often unable to communicate, placing the onus on clinicians in ICUs to engage family members. In the United States, practice has gradually shifted toward including family members in ICU rounds (1). However, the novel coronavirus disease (COVID-19) pandemic dramatically altered hospital care in the United States. For example, early reports suggested many hospitals restricted access to visitors (2). We sought to understand changes to visitation policies and strategies used to communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 11 publications
2
95
0
10
Order By: Relevance
“…In addition, patients and families had minimal face-to-face interaction with their healthcare team, with less than half of patients and families having face-to-face goals-ofcare discussions. These findings likely reflect the impact of restricted visitation policies established during the pandemic, both in Michigan and elsewhere (7,8). In addition, despite the wide availability of videoconferencing tools (9), videoconferencing was rarely used for discussing goals-of-care.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, patients and families had minimal face-to-face interaction with their healthcare team, with less than half of patients and families having face-to-face goals-ofcare discussions. These findings likely reflect the impact of restricted visitation policies established during the pandemic, both in Michigan and elsewhere (7,8). In addition, despite the wide availability of videoconferencing tools (9), videoconferencing was rarely used for discussing goals-of-care.…”
Section: Discussionmentioning
confidence: 92%
“…Although technology and time constraints may threaten human connection in the hospital at the best of times ( 1 ), compassionate end-of-life care for critically ill patients has seldom been more challenging than during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic ( 2 ). The mortality associated with serious infection necessitated public health measures to restrict family presence in the hospital and to conserve limited quantities of personal protective equipment (PPE) ( 3 , 4 ). The devastation of SARS-CoV-2 has separated patients from families ( 5–8 ) and created professional angst ( 9–11 ), particularly when caring for dying patients who are alone in grappling with their grief.…”
mentioning
confidence: 99%
“…The devastation of SARS-CoV-2 has separated patients from families ( 5–8 ) and created professional angst ( 9–11 ), particularly when caring for dying patients who are alone in grappling with their grief. Relatives unable to be with a hospitalized loved one report that they fear not being there to tell clinicians what the patient is “really like” ( 3 ).…”
mentioning
confidence: 99%
“…A survey of intensive care units in the United States found that nearly all hospitals implemented “no-visitor” policies, with certain exceptions at the end-of-life. 58 Strict visitation policies were also implemented by the National Health Service in the United Kingdom. 59 In Taiwan, most hospitals changed visiting policies, with some implementing no-visitor policies and others restricting the number of visitors and visiting hours, paired with symptom and temperature monitoring to screen visitors.…”
Section: Questionsmentioning
confidence: 99%